2005
DOI: 10.1038/sj.onc.1208406
|View full text |Cite
|
Sign up to set email alerts
|

Cell-autonomous induction of functional tumor suppressor 15-lipoxygenase 2 (15-LOX2) contributes to replicative senescence of human prostate progenitor cells

Abstract: Normal human prostatic (NHP) epithelial cells undergo senescence in vitro and in vivo, but little is known about the tissue-specific molecular mechanisms. Here we first characterize young primary NHP cells as CK5 þ /CK18 þ intermediate basal cells that also express several other putative stem/progenitor cell markers including p63, CD44, a2b1, and hTERT. When cultured in serum-and androgen-free medium, NHP cells gradually lose the expression of these markers, slow down in proliferation, and enter senescence. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(91 citation statements)
references
References 33 publications
1
90
0
Order By: Relevance
“…The consequence of increased apoptosis in luminal cells and increased proliferation in basal intermediate cells then resulted in less differentiated yet larger primary tumors in the ventral prostate of pes-ARKO-TRAMP mice than tumors from 16-week-old TRAMP mice (Niu et al, 2008b). The primary prostate tumors of pes-ARKO-TRAMP mice exhibited a higher population of CD44-positive (Liu et al, 2004;Bhatia et al, 2005) and CK5/CK8-positive (van Leenders and Schalken, 2003;Bhatia et al, 2005) intermediate-like cells than those found in wild-type TRAMP mice (Niu et al, 2008a). Incidentally, CD44-positive, but ARnegative prostate cancer cells purified from human prostate cancer xenografts were also enriched in tumorigenic and metastatic progenitor cells (Patrawala et al, 2006).…”
Section: Ar Dual Functions In Prostate Cancer Progression and Metastasismentioning
confidence: 99%
“…The consequence of increased apoptosis in luminal cells and increased proliferation in basal intermediate cells then resulted in less differentiated yet larger primary tumors in the ventral prostate of pes-ARKO-TRAMP mice than tumors from 16-week-old TRAMP mice (Niu et al, 2008b). The primary prostate tumors of pes-ARKO-TRAMP mice exhibited a higher population of CD44-positive (Liu et al, 2004;Bhatia et al, 2005) and CK5/CK8-positive (van Leenders and Schalken, 2003;Bhatia et al, 2005) intermediate-like cells than those found in wild-type TRAMP mice (Niu et al, 2008a). Incidentally, CD44-positive, but ARnegative prostate cancer cells purified from human prostate cancer xenografts were also enriched in tumorigenic and metastatic progenitor cells (Patrawala et al, 2006).…”
Section: Ar Dual Functions In Prostate Cancer Progression and Metastasismentioning
confidence: 99%
“…Basal cells express cytokeratin 5 (CK5), CK14, Bcl-2 (McDonnell et al, 1992), Her-2/neu (Reiter and Sawyers, 2001), p63 (Signoretti et al, 2000), and CD44 (Liu et al, 1997), whereas differentiated luminal cells express CK8, CK18, AR (androgen receptor), prostate-specific antigen (PSA), prostatic acid phosphatase (PAP), CD57, and 15-lipoxygenase 2 (Tang et al, 2002;Bhatia et al, 2005). The basal cell compartment is thought to contain stem/ progenitor cells as >80% of the proliferating cells are localized in the basal layer (Bonkhoff et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…33 Tang et al 21 reported that 15S-HETE at non-physiologically high concentrations (X25 mM) induces apoptosis in prostate cancer cells, but in the presence of exogenous AA, the 15-LOX-2 stable clones showed a significant increase in apoptosis. 22 Most recently, Subbarayan et al 34 found that a relatively low concentration of 15S-HETE (1 or 5 mM) was sufficient for PPARg activation in the presence, but not in the absence of 15-LOX-2 expression, in epithelial cells and cancer cells of prostate. We showed significant induction of apoptosis by restored expression of 15-LOX-2 (in the presence of exogenous AA) in the HNC cells transfected with the 15-LOX-2 expression vector (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding nuclear targeting of 15-LOX-2 might conceptually provide an explanation to the tumor suppressing function of 15-LOX-2. The previous study 22 claimed that one 15-LOX-2 splice variant (15-LOX2sv-b) inhibits tumor growth of prostate cancer cells, but has reduced nuclear targeting and/or no AA metabolizing activity. It is noted that this variant contains a deletion of two exons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation